Site-specific construction of triptolide-based antibody-drug conjugates. (1st December 2021) - Wei, Ding; Mao, Yurong; Xu, Zili; Chen, Jiakang; Li, Jiusheng; Jiang, Biao; Chen, Hongli
Graphical abstract: Abstract: Antibody-drug conjugates (ADCs) have emerging as efficient agents to target deliver cytotoxic drugs and reduce their off-target side effects. Triptolide has attracted attention to be used in ADC development. Herein, three rationally designed triptolide drug-linkers have been synthesized for use in site-specific construction of ADCs. Carbamates that were supposed to be more stable than carbonates were introduced to attach triptolide to the linkers. PEG and discrete PEG chains were incorporated to improve the hydrophilicity of drug-linkers. The ADCs were finally site-specifically prepared by conjugation of the drug-linkers to trastuzumab through disulfide re-bridging approach. The preliminary anti-tumor activities of these ADCs were evaluated and they displayed high potencies against HER2-targeted cancer in vitro and in vivo .